Automated rf-PERTE System for Room Temperature Deposition of TCO Coatings. (December 2016) - Fernandes, M.; Vygranenko, Y.; Vieira, M.; Lavareda, G.; Carvalho, C. Nunes de; Amaral, A.
Abstract: In this work we present a fully automated plasma-enhanced reactive thermal evaporation system (rf-PERTE) that can be used for the deposition of transparent metal oxide films without intentional heating of the substrate. The system and developed software enables the full control over critical deposition conditions such as mass flow of oxygen, process pressure, current flowing through crucible and rf-power. These parameters are automatically adjusted during the deposition thus keeping them in a narrow process window. This way, highly transparent and conductive coating can be deposited with a high degree of reproducibility of the optical and electrical characteristics. The resistivity of 9×10 -4 Ω-cm and the peak transmittance of 90% in the visible spectral range were achieved for indium oxide films deposited on glass substrates. This technique is also suitable for the deposition of transparent conducting coatings in a wide range of plastic materials for flexible solar cells. In particular, we have successfully deposited indium oxide on PEN (polyethylene naphthalate) sheets with electrical and optical properties approaching the ones for films on glass.